JunB–HBZ nuclear translocation by TGF-β is a key driver in HTLV-1-mediated leukemogenesis - Wenyi Zhang; Takafumi Shichijo; Xueda Chen; Miho Watanabe; Kisato Nosaka; Masao Matsuoka; Jun-ichirou Yasunaga (Proceedings of the National Academy of Sciences, 2025)
The HTLV-1 bZIP factor ( HBZ ) gene, which is the only viral gene conserved and consistently expressed in all adult T-cell leukemia–lymphoma (ATL) cases, is critical for ATL oncogenesis. Although HBZ protein is found in both the nucleus and the cytoplasm, the dynamics of HBZ protein localization and its contribution to oncogenesis have not been fully elucidated. In this study, we analyzed the subcellular expression pattern of HBZ in primary HTLV-1–infected T cells from asymptomatic carriers and leukemic cells of ATL patients using the Proximity Ligation Assay. Nuclear localization of HBZ protein was significantly higher in fresh ATL cells than in HTLV-1–infected cells from carriers. Importantly, translocation of HBZ protein from the cytoplasm to the nucleus after TGF-β activation was observed in ATL patients, but not in HTLV-1 carriers. In ATL cells, the cellular transcription factors JunB and pSmad3 interact with HBZ and facilitate its nuclear translocation upon TGF-β stimulation. JUNB knockdown inhibits cell proliferation in vitro and in vivo and promotes apoptosis in ATL cells but not in HTLV-1–infected nonleukemic cells, indicating that JunB has important roles in maintaining ATL cells. In conclusion, TGF-β-induced nuclear translocation of HBZ–JunB complexes is associated with ATL oncogenesis.